The Influence of Marketing, Pricing and Promotion on Gen Z’s Purchase Behaviour of Halal Cosmetics in Indonesia - Mulyono Jamal; Nurul Adila Hasbullah; Adlin Masood; Norfhadzilahwati Rahim (USIM Press, 2024)
Vol. 20, No. 2